1985
DOI: 10.3109/00365528509089690
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Study of the Clinical Course in 186 Patients

Abstract: A series of 186 patients treated for Crohn's disease during the period 1956 to 1968 has been followed up in 1970, 1975, and now in 1983. Among 173 patients operated on there were 89 recurrences (52%). After a follow-up time greater than 14 years (mean, 18 years) 'radical' resections at the first operation gave a lower recurrence rate (31%), fewer reoperations, and a better quality of life compared with non-'radical' resections (recurrence rate, 83%). The quality of life estimated for all patients alive in 1983… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Two retrospective Swedish studies suggested that "radical" resection resulted in a much lower rate of recurrence. Krause et al [22] studied 186 patients with uninvolved bowel margins of less than or greater than 10 cm (a radical resection) and reported a 31% recurrence rate and a better quality of life with radical resection, compared with an 83% recurrence rate in the other group. Softley et al [23] used a 4-cm histologic margin and found that involvement of this margin resulted in a 10-fold increase in recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…Two retrospective Swedish studies suggested that "radical" resection resulted in a much lower rate of recurrence. Krause et al [22] studied 186 patients with uninvolved bowel margins of less than or greater than 10 cm (a radical resection) and reported a 31% recurrence rate and a better quality of life with radical resection, compared with an 83% recurrence rate in the other group. Softley et al [23] used a 4-cm histologic margin and found that involvement of this margin resulted in a 10-fold increase in recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…One possi ble explanation is an impaired lymph drain age in the radical group after extended mes enteric and lymph node resection. In other reports a rather lower recurrence rate is re ported after radical resection than after non radical operation [ 15,25], However, most of these trials were not prospective, the opera tive procedure and the follow-up were not defined by a protocol and the definition of recurrence was used differently [16]. In the OMGGE study the distance of disease-free margin was > 10 cm or alternatively < 4 cm including patients in whom excision was through diseased tissue [25], The influence of location of disease on recurrence after sur gery as described by others [29] did not play a role in our trial since almost all had ileoce cal involvement, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Both strategies were additive: nonradical operation and sulfasalazine had the best prognosis, radical operation and placebo was worst. It is concluded that postoperative recur rence is best prevented by resecting nonradically and prescribing 3 g of sulfasalazine daily at least over 2 years.Approximately 90% of patients suffering from Crohn's disease (CD) will eventually be operated because of complications of their disease during the course of their illness [7,15,21]. Resection does not cure the disease and the rate of recurrence is high [8,9,18,20], Early recurrence is common and could be demonstrated within 1 year postoperatively in 70% of patients progressing from early and limited inflammatory lesions…”
mentioning
confidence: 99%
“…Trotz einiger weniger gegenteiliger Studien [12] scheint die überwältigende Mehrzahl prospektiver und retrospektiver Studien (Übersicht bei [2,44]) darzulegen, daû es keinen Vorteil gibt, Sicherheitsabstände einzuhalten, die über den makroskopisch gesunden Resektionsrand hinausgehen. Dies wird insbesondere unterstützt durch die nicht erhöhte lokale Rezidivrate nach Strikturoplastik, wo definitionsgemäû sogar makroskopisch befallene Areale anastomosiert werden [23,30].…”
Section: Sicherheitsabstand/radikalitätunclassified